Nell’abisso dell’uniforme. Guerra, pace e tecnica nel pensiero di Martin Heidegger - Spina, Salvatore (Filosofia, 2023)
The aim of the paper is to examine the ontological relationship between war and peace in Heidegger’s thought of technology. Through the analyses of some passages of Overcoming metaphysics and Geschichte des Seins, it tries to show how, in an ontological view, war and peace are the Same [das Selbe]. They are two manifestations of a unique complex phenomenon: the domination of technology as expression of forgetfulness of Being [Seinsvergessenheit]. Crosswise the paper aims to present Heidegger’s critical position toward Nazism, considered as manifestation of Western nihilism.